Measurement of Radioactivity Levels in Daily Intake Foods of Erbil City Inhabitants - Ahmed, Ali Hassan; Samad, Ahmed Ismael (Sulaimani Journal for Pure and Applied Sciences, 2014)
This work investigates the natural 226Ra,232Th,40K, 222Rn,220Rn and man-made137Cs radionuclides in foodstuff elements consumed by Iraqi Kurdistan region population (Erbil).The measurements were carried out by using a high efficiency NaI(TI) gamma-ray spectrometerandCR-39 solid state nuclear track detectors. The estimated average activity concentrations in foodstuff were found to be0.17Bq kg-1 for 226Ra, 0.183 Bq.kg-1 for 232Th, 515.5Bq kg-1 for 40K, 0.11Bq.kg-1 for 137Cs and 108.46Bq.m-3 for 222Rn.The total annual internal dose resulting from ingestion of radioisotopes in foodstuff was ranged from 0.01μSv.year-1 to 270.8μSv.year-1whichlies within the standard safety range of consumption. Keywords: Radioactivity, gamma spectroscopy, CR-39, Foodstuff.
Keywords: Radioactivity; gamma spectroscopy; CR39; Foodstuff